2017
DOI: 10.5585/exactaep.v15n4.6956
|View full text |Cite
|
Sign up to set email alerts
|

Análise da qualidade em um restaurante universitário através da ferramenta SERVQUAL

Abstract: O setor de serviços destaca-se mundialmente como um dos maiores geradores de renda, o que indica, em si tratando de um ambiente cada vez mais dinâmico e competitivo, que a qualidade atrelada a este atua como diferencial de mercado e influencia diretamente na sobrevivência da empresa. Este trabalho, portanto, utilizou uma adaptação do modelo SERVQUAL visando mensurar a qualidade do serviço prestado por um Restaurante Universitário. Um questionário foi desenvolvido e aplicado buscando avaliar as diferenças entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
1
0
6
Order By: Relevance
“…In our study, the highest values of cumulative variance were observed in the factors referring to the menu, which makes sense, since being a meal-serving place, the menu is the main reason to satisfy the diner (Araújo et al, 2017). Kim, Lee, Yuan (2012) in a study conducted with university students in South Korea found that the link between "food" and the overall satisfaction of the diner were the strongly significant variables and concluded that the food factor generates a higher level of satisfaction of the diners with the food service.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In our study, the highest values of cumulative variance were observed in the factors referring to the menu, which makes sense, since being a meal-serving place, the menu is the main reason to satisfy the diner (Araújo et al, 2017). Kim, Lee, Yuan (2012) in a study conducted with university students in South Korea found that the link between "food" and the overall satisfaction of the diner were the strongly significant variables and concluded that the food factor generates a higher level of satisfaction of the diners with the food service.…”
Section: Discussionsupporting
confidence: 49%
“…The UC serves any individual on campus; however, students were the most frequent (97%) diners, as was also noted by Araújo et al, (2017) in Brazil and Serhan, Serhan (2019) at a university in Lebanon. In college cafeterias in Brazil, students pay a minimum amount and the balance payment is transferred by the University to the catering companies.…”
Section: Discussionmentioning
confidence: 65%
“…Mas inúmeros outros temas são estudados, como qualidade de atendimento em saúde a animais em clínicas veterinárias (Gregório, Santos, Pires, Prada & Queiroga, 2016); motivação de pacientes para adesão à terapia com insulina (Jakupovic, Solakovic, Celebic & Kulovic, 2018); percepção da qualidade de atendimento em postos de combustíveis (Sampaio Barbosa, Rabelo Neto, Nunes Moreira & de Almeida Bizarria, 2016); qualidade de serviços em clínica de atendimento a usuários de drogas (Naqavi, Refaiee, Baneshi & Nakhaee, 2014); em serviços de logística e transportes (Feitosa;Colona;& Kelch, 2017); serviços de transporte (Maksimović Mlađan, Đorđević Bojan, Brzaković Miodrag & GrahovacMiloš, 2017); em serviços de um restaurante universitário (Araújo, Melo Filho, Pinto, Machado & Castro Silva, 2017); academia de ginástica ; hospedagem em festejos populares (Macêdo, Alves de Paula, Cardoso, Souza Valdevino & de Souza Ferraz, 2013); entre outros temas que aparecem em inúmeros artigos.…”
Section: Procedimentos Metodológicosunclassified
“…As Unidades de Alimentação e Nutrição (UAN) são estabelecimentos responsáveis pela produção e distribuição refeições para coletividade e tem por objetivo oferecer aos comensais uma alimentação nutricionalmente equilibrada, atendendo as características sensoriais e higiênico-sanitárias que possam auxiliar na recuperação e/ou manutenção da saúde da coletividade contribuindo, dessa forma, para o desenvolvimento de hábitos alimentares saudáveis, além de oferecer também uma alimentação de custo acessível para estudantes ARAÚJO et al, 2017).…”
Section: Introductionunclassified
“…Dentre as informações necessárias para o efetivo controle e avaliação do desempenho de uma unidade, a mensuração das perdas é uma das mais importantes, pois viabiliza a detecção das práticas que geram aumento dos gastos e desperdícios desnecessários (ABREU, SPINELLI e PINTO, 2016;ARAÚJO et al, 2017).…”
Section: Introductionunclassified